POST-DISCHARGE SURGICAL SITE INFECTION: OCCURRENCE AND CHARACTERIZATION OF GENERAL SURGERY OUTPATIENTS - Raíssa Gabriela dos Reis; Maria Cristina Soares Rodrigues (Universidade Federal do Paraná, 2017)
The objective of this study was to investigate the occurrence of surgical site infection and describe the characteristics of cases of general surgery outpatients in post-discharge follow-up in a hospital in the Federal District, in Brazil. This was a descriptive, retrospective study corresponding to the years 2011 to 2013, conducted from August 2015 to July 2016, based on consulting the hospital's information systems and the medical records of patients. In the study period, 2,772 general surgery procedures were performed and 2,283 (82.28%) patients received post-discharge follow-up. Eighty-five cases of infection were diagnosed, equivalent to a mean rate of 3.7% in the period. There was a higher occurrence of infection between the sixth and tenth day after surgery. The data reinforces the relevance of post-discharge surveillance instituted in the health service and provides results indicators that may help define strategies for improving measures aimed at preventing and controlling surgical site infections.